A biochemical investigation into the compounds involved in pigmentation of apple and pear skin and the manipulation thereof - Arends, Arrie Paul (Stellenbosch : Stellenbosch University, 2012)
Thesis (M. Sc.) -- University of Stellenbosch, 1998.